Population-based outcomes by immunosuppressed status in patients undergoing radiotherapy for oropharyngeal cancer. (October 2020) - Hamilton, Sarah Nicole; Urban, Ryan; Liu, Alvin; Chau, Nicole; Berthelet, Eric; Tran, Eric; Wu, Jonn; Yin, Yaling; Olson, Robert
Highlights: 5.8% of oropharynx cancer patients had a history of immunosuppression prior to diagnosis. Immunosuppression was an independent risk factor for worse disease free survival in oropharyngeal cancer patients treated with radiotherapy. Abstract: Introduction: The incidence of immunosuppression in patients with oropharynx head & neck squamous cell carcinoma (SCC) is not well studied. This study evaluates disease characteristics and treatment outcomes in oropharynx SCC in patients with and without immunosuppression. Methods: A retrospective review of all patients treated with radiotherapy for oropharynx SCC at BC Cancer from 2011 to 2016 was performed. Survival outcomes were assessed using Kaplan-Meier methods and competing risk analysis. Multivariate analysis and propensity score matching were performed. Results: There were 1077 patients, of which 5.8% ( n = 62) had an immunosuppressive medical condition or were taking long-term immunosuppressive medication at diagnosis. Median follow-up was 3.3 years. Three year OS for patients without immunosuppression was 79.5% (95% Confidence Interval [CI] 76.8–82.0%) and for those with immunosuppression was 64.6% (95% CI 50.9–75.3%) (hazard ratio [HR] 1.78, 95% CI 1.18–2.68, p = 0.0062). The three year disease recurrence for patients without immunosuppression was 24.9% (95% CI 22.2–27.7%) and 44.4% (95% CI 31.5–56.6%) for those with immunosuppression (HR 2.12, 95% CI 1.45–3.11, p = 0.0001). Multivariate analysis of disease free survival (DFS) found that active smoking, advanced TNM stage, base of tongue subsite, p16 negative and unknown, no concurrent chemotherapy, higher Charlson Comorbidity Index, and lower radiation dose were also associated with worse DFS (all p < 0.05). Immunosuppressed patients had worse DFS relative to patients without immunosuppression, p < 0.001, HR 1.97 (95% CI 1.33–2.91). Conclusion: Immunosuppression was an independent predictor of worse DFS in this large cohort of patients with oropharynx SCC.